Light-Responsive Oxadiazole-Based (Hetero)aryl-azobenzenes - Enache, Bogdan C.; Simene, Adela F.; Hanganu, Anamaria; Tablet, Cristina; Mădălan, Augustin M.; Popescu, Codruta C.; Matache, Mihaela (Synthesis, 2025)
Switching molecules under light irradiation has become a very popular topic to attain interconvertible states with different properties. Fine-tuning of molecular structures can lead to very interesting compounds and by combining various motifs, novel light-responsive molecules can be prepared. We describe herein the design and synthesis of novel (hetero)aryl-azo derivatives in the form of oxadiazole-decorated azobenzenes and oxadiazole-based aryl-azopyrazoles. We studied the behavior of the synthesized compounds under light irradiation, both in terms of photoswitching and emissive properties.
Keywords: Photoswitches; Fluorescence; 1,3,4-Oxadiazole; Arylazopyrazole; Azobenzene